Design of an IoT-Based System for Monitoring Heart Rate and Oxygen Levels at Posyandu Latulif, Rajagaluh Village, Majalengka Regency - Fahririzal Gani Husaini Husaini; Rido Taufiq Subagio; Arif Nursetyo (Kresnamedia Publisher, 2025)
This research was carried out to support improvements in health services at Posyandu Latulif, Rajagaluh Village, Majalengka Regency. Previously, health examinations such as heart rate and blood oxygen level measurements were still conducted manually using conventional tools. This method often takes a long time, is less practical, and causes long queues during Posyandu activities. These challenges become more difficult when there are many patients or when patients wear thick clothing that interferes with the use of manual tensimeters. As a solution, the researcher developed a health monitoring device based on the Internet of Things (IoT) that can measure heart rate and blood oxygen levels in real-time. The system uses a MAX30100 sensor to read biometric data and a NodeMCU ESP8266 microcontroller connected to a WiFi network to process and transmit the results. The data is shown on a 16x2 LCD screen and automatically sent to Google Spreadsheet, allowing Posyandu staff to view and record the results instantly without manual note-taking. This system is designed to be user-friendly and suitable for health workers even without technical backgrounds. Based on testing, the device performed well and was able to produce accurate and stable readings. With this tool, health monitoring activities can be carried out more quickly, efficiently, and with digital documentation. Moreover, the system offers a practical example of how simple and useful technology can be applied to support public health services, especially in rural areas. This process often results in inefficiency because health cadres must first inflate the cuff, wait for the needle to stabilize, record the value manually, and sometimes repeat the measurement if the patient moves. This not only increases examination time but also raises the risk of recording errors. When uploading to Google Spreadsheet, patient data security is maintained by limiting access to authorized Posyandu cadres only, with password-protected accounts. No personal identifiers such as names or addresses are uploaded, ensuring privacy is preserved. Infants were excluded because the MAX30100 fingertip sensor requires stable finger positioning, which is difficult to achieve in babies. However, with sensor adaptation or integration into specialized infant probes, the system can be developed in the future for neonatal or pediatric use. The accuracy of the MAX30100 sensor has been validated in previous studies and was further tested in this project by comparison with a clinical-grade oximeter. The results showed only a small deviation, indicating that the sensor is sufficiently accurate for field conditions.